Melatonin protects against maternal diabetes-associated meiotic defects by maintaining mitochondrial function - Li, Xiao-Qing; Wang, Yi; Yang, Shu-Jie; Liu, Yu; Ma, Xiang; Liu, Lu; Li, Si-Hong; Niu, Dong; Duan, Xing (Free radical biology & medicine, 2022)
Maternal diabetes has been widely reported to adversely affect oocyte quality. Although various molecules and pathways may be involved in this process, strategies to prevent maternal diabetes-induced deterioration of oocyte quality remain unexplored. Melatonin is synthesized by the pineal gland and has been shown to have beneficial effects on oocyte quality owing to its antioxidative function. In the present study, we found that the exposure of oocytes of diabetic mice to melatonin, in vitro, alleviated aberrant oocyte maturation competence. Notably, melatonin supplementation attenuated defects in spindle organization and chromosome alignment by mediating the expression of TPX2 and pericentrin localization. Importantly, melatonin eliminated the accumulation of reactive oxygen species and increased the cytosolic Ca2+ levels in diabetic oocytes by maintaining mitochondrial function. Moreover, the occurrence of autophagy and apoptosis was reversed in diabetic oocytes after melatonin exposure via decreased LC3β expression. Collectively, our findings provide evidence that melatonin supplementation can protect oocytes from maternal diabetes-related meiotic defects and poor egg quality, providing a potential strategy for improving oocyte quality in assisted reproductive technologies. [Display omitted] •Melatonin restores the maternal diabetes-induced deterioration of oocyte quality.•Melatonin improves the oocyte maturation competency of diabetic oocytes.•Melatonin alleviates maternal diabetes-induced mitochondrial dysfunction.•Melatonin suppresses the oxidative stress-induced DNA damage and apoptosis of diabetic oocytes.